Clinical and laboratory predictors of 30‐day mortality in severe acute malnourished children with severe pneumonia. Issue 11 (28th September 2020) - Shahrin, Lubaba; Chisti, Mohammod J.; Brintz, Benjamin; Islam, Zahidul; Shahid, Abu S.M.S.B.; Hassan, Md. Zakiul; Leung, Daniel T.; Chowdhury, Fahmida
Abstract: Objective: To determine the predictors of mortality within 30 days of hospital admission in a diarrhoeal disease hospital in Bangladesh. Methods: Cohort study of hospitalised children aged 0–59 months with severe acute malnutrition (SAM) and severe pneumonia in Dhaka Hospital, icddr, b, Bangladesh from April 2015 to March 2017. Those discharged were followed up, and survival status at 30 days from admission was determined. Children who died were compared with the survivors in terms of clinical and laboratory biomarkers. Multivariable logistic regression analysis was used for calculating adjusted odds ratio for death within 30 days of hospital admission. Results: We enrolled 191 children. Mortality within 30 days of admission was 6% (14/191). After adjusting for potential confounders (hypoxia, CRP and haematocrit) in logistic regression analysis, independent factors associated with death were female sex (aOR = 5.80, 95% CI: 1.34–25.19), LAZ <−4 (aOR = 6.51, 95% CI: 1.49–28.44) and Polymorphonuclear Leucocytes (PMNL) (>6.0 × 10 9 /L) (aOR = 1.06, 95% CI: 1.01–1.11). Using sex, Z‐score for length for age (LAZ), and PMNL percentage, we used random forest and linear regression models to achieve a cross‐validated AUC of 0.83 (95% CI: 0.82, 0.84) for prediction of 30‐day mortality. Conclusions: The results of our data suggest that female sex, severe malnutrition (<−4 LAZ) and higher PMNL percentage were prone to be associated with 30‐day mortality in children with severe pneumonia. Association of these factors may be used in clinical decision support for prompt identification and appropriate management for prevention of mortality in this population. Abstract : Objectif: Déterminer les prédicteurs de mortalité dans les 30 jours suivant l'admission à l'hôpital dans un hôpital pour maladies diarrhéiques au Bangladesh. Méthodes: Etude de cohorte d'enfants hospitalisés âgés de 0 à 59 mois atteints de malnutrition aiguë sévère (MAS) et de pneumonie sévère à l'hôpital de Dhaka, icddr, b, au Bangladesh d'avril 2015 à mars 2017. Ceux qui ont été libérés ont été suivis et leur état de survie à 30 jours de l'admission a été déterminé. Les enfants décédés ont été comparés aux survivants en termes de biomarqueurs cliniques et de laboratoire. Une analyse de régression logistique multivariée a été utilisée pour calculer le rapport de cotes ajusté pour le décès dans les 30 jours suivant l'admission à l'hôpital. Résultats: Nous avons inscrit 191 enfants. La mortalité dans les 30 jours suivant l'admission était de 6% (14/191). Après ajustement pour les facteurs confusionnels potentiels (hypoxie, CRP et hématocrite) dans l'analyse de régression logistique, les facteurs indépendants associés au décès étaient le sexe féminin (aOR = 5, 80 ; IC95%: 1, 34 à 25, 19), LAZ <‐4 (aOR = 6, 51 ; IC95%: 1, 49‐28, 44) et leucocytes polymorphonucléaires (LPMN) (>6, 0 x 10 9 /L) (aOR = 1, 06 ; IC95%: 1, 01‐1, 11). En utilisant le sexe, le score Z de la taille pour l'âge (LAZ) et le pourcentage de LPMN, nous avons utilisé des modèles de régression linéaire et de forest aléatoires pour obtenir une AUC validée croisée de 0, 83 (IC95%: 0, 82‐0, 84) pour la prédiction de la mortalité à 30 jours. Conclusions: Les résultats de nos données suggèrent que le sexe féminin, la malnutrition sévère (LAZ <‐4) et un pourcentage plus élevé de LPMN étaient susceptibles d'être associés à la mortalité à 30 jours chez les enfants atteints de pneumonie sévère. L'association de ces facteurs peut être utilisée dans l'aide à la décision clinique pour une identification rapide et une prise en charge appropriée pour la prévention de la mortalité dans cette population.